A Fast Computational Algorithm for the Discrete Sine Transform - Yip, P.; Rao, K. (IEEE transactions on communications, 1980)
A sparse-matrix factorization is developed for the discrete sine transform (DST). This factorization has a recursive structure and leads directly to an efficient algorithm for implementing the DST, a feature most desirable and very similar ot that of the DCT. This algorithm requires fewer arithmetic operations compared to that for the discrete cosine transform (DCT).